Integrasi RCM Dan TPM Untuk Meningkatkan Keandalan Mesin Homogenizer - Muhammad Ikhsanudin Basri; Rakay Edhiargo Toyosito; Lifia Citra Ramadhanti (UNIVERSITAS ISLAM SYEKH YUSUF TANGERANG, 2026)
The homogenizer is one of the critical machines in the NonDairy Creamer production process due to its role in producing stable and uniform emulsions. Frequent failures in the homogenizer can increase downtime and reduce production effectiveness. This study aimed to identify critical components causing downtime, determine appropriate maintenance strategies using the Reliability Centered Maintenance (RCM) approach, and evaluate the impact of Total Productive Maintenance (TPM) implementation on homogenizer reliability at PT CRM. The research methods included downtime analysis, calculation of Mean Time To Failure (MTTF) and Mean Time To Repair (MTTR), Failure Mode and Effect Analysis (FMEA), Logic Tree Analysis (LTA), and the development of maintenance strategies based on RCM integrated with TPM. The results showed that the homogenizer contributed 2,007 minutes or 69% of total production downtime. The most critical component was the plunger gasket with a Risk Priority Number (RPN) of 504. The implementation of the proposed maintenance strategy reduced downtime by 69%, decreased failure frequency by 67%, increased MTTF from 4,623.75 minutes to 13,871.25 minutes, and reduced MTTR from 83.63 minutes to 76.25 minutes. These findings indicate that the integration of RCM and TPM effectively improves homogenizer reliability and supports sustainable production performance.